Au-ZnO: a tunable localized surface plasmonic nanocomposite - Mishra, Y. K.; Mohapatra, S.; Singhal, R.; Avasthi, D. K.; Agarwal, Dinesh C.; Ogale, S. B. (Applied Physics Letters, 2008)
In this letter, we report the thermal processing controlled tunability of localized surface plasmon resonance (LSPR) of Au nanoparticles embedded in ZnO matrix. Au-ZnO nanocomposite films were prepared by atom beam cosputtering and were annealed from 200 to 600 degrees C in Ar. A regular redshift similar to 110 nm (from 505 to 615 nm) in LSPR peak with increase in annealing temperature up to 600 degrees C is observed. Transmission electron microscopy results confirm the formation of Au nanoparticles supported by ZnO nanorods at annealing temperature of 600 degrees C. The Au-ZnO nanocomposite exhibits significant enhancement in the Raman signal for C(70) molecules. (C) 2008 American Institute of Physics.